LRPPRC: A Multifunctional Protein Involved in Energy Metabolism and Human Disease - Cui, Jie; Wang, Li; Ren, Xiaoyue; Zhang, Yamin; Zhang, Hongyi (Frontiers in Physiology, 2019)
The pentatricopeptide repeat (PPR) family plays a major role in RNA stability, regulation, processing, splicing, translation, and editing. Leucine-rich PPR-motif-containing protein (LRPPRC), a member of the PPR family, is a known gene mutation that causes Leigh syndrome French–Canadian. Recently, growing evidence has pointed out that LRPPRC dysregulation is related to various diseases ranging from tumors to viral infections. This review presents available published data on the LRPPRC protein function and its role in tumors and other diseases. As a multi-functional protein, LRPPRC regulates a myriad of biological processes, including energy metabolism and maturation and the export of nuclear mRNA. Overexpression of LRPPRC has been observed in various human tumors and is associated with poor prognosis. Downregulation of LRPPRC inhibits growth and invasion, induces apoptosis, and overcomes drug resistance in tumor cells. In addition, LRPPRC plays a potential role in Parkinson's disease, neurofibromatosis 1, viral infections, and venous thromboembolism. Further investigating these new functions of LRPPRC should provide novel opportunities for a better understanding of its pathological role in diseases from tumors to viral infections and as a potential biomarker and molecular target for disease treatment.